Study on the impact of the COVID-19 pandemic on stunting program implementation (sensitive and specific programs) in Sleman Regency - Gifani Rosilia; Renita Renita; Riyanti Dina Kusuma; Dewi Nugraha Primastuti; Siti Helmyati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
The COVID-19 pandemic is a new challenge for the implementation of stunting intervention in Indonesia. Therefore, monitoring the stunting program implementation during a pandemic is crucial to achieving the target of stunting reduction. This research aims to examine the pandemic’s impacts on the implementation of specific and sensitive programs, especially posyandu, iron supplementation, PMT, and Sustainable Food Program(SFG). Method, qualitative research uses a Case-Study with 17 informants selected by purposive sampling, including the stakeholders and program’s target in the working area of Tempel 2 Health Center. Data in the form of interview transcripts and other documents were collected using in-depth interviews and documentation studies in November-December 2021 and were analyzed in 3 stages: reduction, presentation, and conclusion. Result, the COVID-19 pandemic has affected specific nutrition interventions, especially in the planning, implementation, and scope of activities. It relates to social difficulties and concerns over the spread of COVID-19. In the implementation of SFG program, the pandemic does not have a significant impact. It can be interpreted that COVID-19 pandemic affects several aspect of the stunting program’s implementation. This study suggests the stakelhoders and communities to optimize the implementation of stunting intervention so it can run sustainably to reduce stunting prevalences.